2021
DOI: 10.1155/2021/1951364
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Change Rates of CYFRA21-1 and CEA in Predicting Chemotherapy Efficacy for Non-Small-Cell Lung Cancer

Abstract: Background. Cytokeratin 19 fragment 21-1 (CYFRA21-1) and carcinoembryonic antigen (CEA) are effective prognostic biomarkers for lung cancer. This study investigated the predictive effects of change rates of CYFRA21-1 and CEA before and after the first cycles of chemotherapy on advanced IIIb/IIIc or IV stage non-small-cell lung cancer (NSCLC) patients. Methods. Data of 103 NSCLC patients who received chemotherapy in Zhejiang Provincial People’s Hospital from February 2018 to November 2020 were retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The killing of cancer cells by radiotherapy or chemotherapy and targeted drugs can delay the recurrence and metastasis of tumors on the basis of reducing tumor foci, thereby improving the long-term prognosis of the disease. CEA, CYFRA21-1, SCCA have been proven to be serum tumor markers for early diagnosis of lung cancer [34] [35] . CEA is an acid glycoprotein produced by colorectal cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The killing of cancer cells by radiotherapy or chemotherapy and targeted drugs can delay the recurrence and metastasis of tumors on the basis of reducing tumor foci, thereby improving the long-term prognosis of the disease. CEA, CYFRA21-1, SCCA have been proven to be serum tumor markers for early diagnosis of lung cancer [34] [35] . CEA is an acid glycoprotein produced by colorectal cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%